PERJANJIAN KERJASAMA ANTARA DEALER MOBIL PT. MAHAKAM BERLIAN SAMJAYA DENGAN PERUSAHAAN FINANCE PT. CLIPAN FINANCE SAMARINDA DALAM HAL JUAL BELI MOBIL - Ferny Meirinda Lestari (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
Abstract This study aims to determine the form of cooperation agreement and form of accountability of the parties in cooperation between dealers PT. Mahakam Berlian Samjaya with PT. Clipan Finance Samarinda. The results of the study show the form of a cooperation agreement between PT. Mahakam Berlian Samjaya with PT. Clip Finance Samarinda is a written agreement based on an agreement with the principle of freedom of contract, where both are entitled to freely determine the form and content of the agreement as stipulated in Article 1338 Paragraph(1) of the Civil Code. While the accountability of the parties has been clearly stated in the cooperation agreement, where Indomobile Finance is obliged to carry out analysis and verification that are deemed necessary and in accordancewith the operational standards for each application submitted by the dealer before finally being approved by PT. Clipan Finance Samarinda, where the rights and obligations of the dealer and the financing company have been in compliance with the rights and obligations of the business actor in the Consumer Protection Act.Keywords: cooperation agreements, car dealers, finance companies